Achieving Uniform Carrier Distribution in MBE-Grown Compositionally Graded InGaN Multiple-Quantum-Well LEDs - Pawan Mishra; Bilal Janjua; Tien Khee Ng; Chao Shen; Abdelmajid Salhi; Ahmed Y. Alyamani; Munir M. El-Desouki; Boon S. Ooi (IEEE Photonics Journal, 2015)
We investigated the design and growth of compositionally graded InGaN multiplequantum-well (MQW)-based light-emitting diodes (LEDs) without an electron-blocking layer. Numerical investigation showed uniform carrier distribution in the active region and higher radiative recombination rate for the optimized graded-MQW design, i.e., In0→xGa1→(1-x)N/InxGa(1-x)N/Inx→0Ga(1-x)→1N, as compared with the conventional stepped-MQW-LED. The composition-grading schemes, such as linear, parabolic, and Fermi-function profiles, were numerically investigated for comparison. The stepped- and graded-MQW-LEDs were then grown using plasma-assisted molecular beam epitaxy through surface-stoichiometry optimization based on reflection high-energy electron diffraction in situ observations. Stepped- and graded-MQW-LED showed efficiency roll over at 160 and 275 A/cm2, respectively. The extended threshold current density rollover (droop) in graded-MQW-LED is due to the improvement in carrier uniformity and radiative recombination rate, which is consistent with the numerical simulation.